Analisis Balaghah Pada At-Thibaq Ilmu Badi' dalam Surat Al-Isra': dan Desain Pembelajarannya - Ervia Arum Yuniarti; Fachrul Ghazi; Zulhannan; Muhammad Akmansyah (Universitas KH. Mukhtar Syafaat, 2026)
Balaghah is the science that discusses how to convey meaning accurately and beautifully, while at-tibaq in the science of bad?‘ is a style of language that emphasizes the contrast between two opposing meanings in a text, including in the verses of Surat Al-Isra’. This is the key to understanding the depth of meaning and beauty of the language of the Qur’an, but it is rarely used systematically as the basis for learning design. Therefore, this study aims to analyze the form and function of at-tibaq in Surah Al-Isra' and formulate a text-based Balaghah learning design and case method. The method used is a qualitative approach in the form of a literature study, with the main data being verses from Surah Al-Isra' that contain at-tibaq and related scientific articles, analyzed through content analysis. The results of this study show that there are several types of at-tibaq (contradictions in meaning between verses, within a phrase, within a sentence, and in semantic roles) that serve to emphasize dichotomies of meaning, clarify moral consequences, and strengthen the persuasive, emotional, and aesthetic power of the text. The contribution to the development of Balaghah learning is evident when the verses of Al-Isra' are used as the main case for analysis, arranged in a step-by-step module, and enriched with lesson plan design tasks so that Balaghah material is easier to understand and closer to the learning experience.